Selection and use of a Saccharomyces cerevisae strain to reduce phytate content of wholemeal flour during bread-making or under simulated gastrointestinal conditions. Issue 1 (September 2015) - Caputo, L.; Visconti, A.; De Angelis, M.
Abstract The aim of this work was to select a yeast able to hydrolyse phytate during bread-making or under simulated gastro-intestinal (GI) conditions. High levels of cell-bound and intracellular phytate-degrading enzyme activities were found in Saccharomyces cerevisiae LC3, selected among 16 yeast strains. Phytase enzyme of LC3, purified by three chromatographic steps, had a molecular weight of ca. 48 kDa; its optimal activity, displayed on sodium phytate, was at pH 5.0 and at 40 °C. S. cerevisiae LC3 was used together with negative phytase producing Lactobacillus plantarum LP41 to make wholemeal bread that showed a marked decrease (ca. 79%) in phytate content in comparison with bread produced with commercial baker's yeast and the same Lactobacillus strain. In addition, S. cerevisiae LC3 survived and hydrolysed phytate under simulated GI conditions. The results of this study indicate that the selected LC3 could be a promising candidate to be used as starter for the reduction of phytate content of wholemeal flour during bread-making or as a probiotic for human or animal applications.